1 The Public Records of the Colony of Connecticut 95-96 (J. Hammond Trumbull ed., 1850) (enacted 1643) - (:unkn) unknown (My University, 1643)
Required each family to bring arms to church every Sabbath and lecture day.
Keywords: REQUIRED POSSESSION